Hepatitis A vaccination - Zhang, Li (Human vaccines & immunotherapeutics, 2020)
Hepatitis A is an important public health issue worldwide. Hepatitis A vaccine (HepA) was first licensed in 1992. Both inactivated HepA (HepA-I) and live attenuated HepA (HepA-L) are highly immunogenic and well tolerated, and immune protection postvaccination can persist for at least 20 y. HepA is effective for both preexposure and postexposure prophylaxis, especially among children and young adults. The strategy of HepA vaccination varies in different countries and mainly includes vaccination among high-risk populations, regional childhood vaccination and universal childhood vaccination. The incidence of hepatitis A has decreased greatly in many countries in the last 30 y, but hepatitis A outbreaks frequently occur among high-risk populations and those who have not been covered by universal child vaccination programs in recent years. Disease surveillance and serosurveys are suggested to clarify the shift in the epidemiology of hepatitis A. The long-term persistence of immune protection after one dose of HepA should be further studied, as well as the cost-effective evaluation of different strategies of HepA vaccination. Based on this evidence, the recommendation on HepA vaccination should be put forward scientifically and updated in a timely and well-implemented manner.